P1-S2.29 Risky sexual practices among youth in Quebec Care Centers. (10th July 2011) - Lambert, Gilles; Haley, Nancy; Jean, Sandrine; Tremblay, Claude; Frappier, Jean-Yves; Otis, Joanne; Roy, Elise
Abstract : Background: Adolescents in Youth Protection facilities are a vulnerable population, with difficult life trajectories; many of their behaviours are health compromising. Method: Youth aged 14–17, living in semi-urban and urban youth centers in Quebec were recruited on a volunteer basis to participate in the study. Socio-demographic, drug use, sexual behaviours and health service utilisation data were obtained using a structured, face-to-face interview. A urine sample was collected to test for chlamydia and gonorrhoea. Results: Between July 2008 and May 2009, 578 youth were interviewed—(♂—58 %); median age—♂—16; ♀—15. The majority of youth were sexually active (89%); two thirds experienced voluntary coitarche before 14 years of age. Median number of lifetime partners was 6 (♂—8, ♀—5). Over a third (41%) reported group sexual activities. A large proportion of youth experienced 50% or more of their sexual activities under the influence of alcohol—18%, cannabis—37%, other drugs—18%. Lifetime history of "never or rarely" using condoms was 24.7% for vaginal relations and 42.1% for anal relations (♂—33%, ♀—55%). Protection used during last vaginal activity was—double protection (condom and another contraceptive method)—25%; condom only—32%; contraceptive method without condom—20%; no protection—24%. A quarter of girls (28%) and boys (27%) reported an unplanned pregnancy (lifetime). Prevalence of chlamydia was—girls 9%, boys 1.9%. No cases of gonorrhoea were documented. Conclusions: Youth in Quebec care centers report many risky sexual behaviours, often associated with drug and alcohol use. Only a quarter of youth used protection to prevention both STIs and pregnancy during their last sexual activity. Their sejour in residential care is an opportune moment to screen these youth for risk behaviours that may compromise their future health and to provide them with personalised prevention education and health services adapted to their reality.